Pengaruh Penilaian Kinerja dan Kompensasi terhadap Disiplin Kerja Karyawan - Salma Putri Adzkia; Sri Suwarsi (UNISBA Press, 2022)
Abstract. The existence of competition in this era of globalization, of course, companies are required to have reliable employees so that they can compete with other competitors. Work effectiveness for employees is an important thing in organizational/company activities which also need to be fostered and developed to achieve organizational goals. This goal can also be achieved if it has quality natural resources, is reliable, has reliable performance, and has good work discipline. This study aims to determine whether there is an influence between the performance appraisal (X1) and the compensation (X2) on work discipline (Y), this study uses descriptive and verification methods, uses a quantitative research approach and operates the calculations using the IBM SPSS program. Collecting data obtained through questionnaires, observations, interviews, and literature studies. The sampling technique is Stratified Random Sampling. Respondents in this study were employees of Wijaya Toyota Dago, totaling 51 employees. The results of this study concluded that: 1) The performance appraisal (X1) on the Wijaya Toyota Dago is included in the High category. 2) The compensation (X2) on the Wijaya Toyota Dagot is included in the High category. 3) Work discipline (Y) in Wijaya Toyota Dago is included in the Very High category. 4) There is an influence of the Performance Appraisal (X1) variable on the Work Discipline (Y) of employees in Wijaya Toyota Dago Bandung 5) There is an influence of the Compensation (X2) variable on the Work Discipline (Y) of employees at Wijaya Toyota Dago Bandung. 6) There is an influence of the Performance Appraisal (X1) and Compensation (X2) on the Work Discipline (Y) of employees at Wijaya Toyota Dago Bandung. Abstrak. Adanya persaingan pada era globalisasi ini, tentu perusahaan dituntut untuk memiliki karyawan yang handal sehingga dapat bersaing dengan pesaing lainnya. Efektivitas kerja bagi para pegawai merupakan suatu hal yang penting dalam kegiatan organisasi/perusahaan yang juga perlu untuk dibina serta dikembangkan untuk tercapainya sebuah tujuan organisasi. Tujuan tersebut juga dapat dituju apabila memiliki sumber daya alam yang berkualitas, handal, memiliki kinerja yang handal, serta disiplin kerja yang baik. Penelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh antara penilaian kinerja (X1) dan kompensasi (X2) terhadap disiplin kerja (Y), penelitian ini menggunakan metode deskirptif dan verifikatif, dengan menggunakan pendekatan penelitian kuantitatif dan mengoperasiokan perhitungannya menggunakan program IBM SPSS. Pengumpulan data yang diperoleh melalui kuesioner, observasi, wawancara, dan studi pustaka. Teknik penarikan sampel adalah Stratified Random Sampling. Responden dalam penelitian ini adalah karyawan Wijaya Toyota Dago yang berjumlah 51 karyawan.Hasil penelitian ini menyimpulkan bahwa: 1) Penilaian kinerja (X1) pada Wijaya Toyota Dago termasuk ke dalam kategori Tinggi. 2) Kompensasi (X2) pada Wijaya Toyota Dago termasuk ke dalam kategori Tinggi. 3) Disiplin kerja (Y) pada Wijaya Toyota Dago termasuk ke dalam kategori Sangat Tinggi. 4) Terdapat pengaruh variabel Penilaian Kinerja (X1) terhadap Disiplin Kerja (Y) karyawan di Wijaya Toyota Dago Bandung 5) Terdapat pengaruh variabel Kompensasi (X2) terhadap Disiplin Kerja (Y) karyawan di Wijaya Toyota Dago Bandung. 6) Terdapat pengaruh Penilaian Kinerja (X1) dan Kompensasi (X2) terhadap Disiplin Kerja (Y) karyawan Di Wijaya Toyota Dago Bandung.